Analysis of the Relationship between Learning Motivation and Students Cognitive Involvement in Problem-Based Learning through Lesson Study on the Material of Speed and Average Rate - Rindy Puspita Anggrini; Lusia Andini; Gita Salsabilla Nurma Yahya; Neneng Lestari; Nova Susanti (Jurnal Pijar MIPA, 2025)
Education in the 21st century emphasizes active student engagement, where intrinsic motivation is expected to emerge as observable cognitive participation, particularly through verbal discussions. However, although Lesson Study (LS) and Problem-Based Learning (PBL) are widely reported to strengthen intrinsic motivation, high motivation does not always translate into high verbal cognitive engagement, indicating a potential mismatch influenced by non-cognitive factors. This study aims to analyze the effectiveness of Lesson Study (LS) and Problem-Based Learning (PBL) in fostering students' intrinsic motivation and identify non-cognitive factors that influence the mismatch between motivation and verbal cognitive engagement. This descriptive study used mixed methods, involving 25 students of the Physics Education Study Program. Data were collected through motivation questionnaires (quantitative) and transcripts of group discussion recordings (qualitative) during the implementation of Lesson Study and PBL and processed using descriptive statistics. The quantitative results showed that students' learning motivation was in the high category across all indicators, including persistence, interest, achievement, and independence. However, the qualitative results of the transcripts of verbal cognitive engagement revealed significant variation, where some students exhibited low verbal activity despite having high motivation levels. This inconsistency suggests that high intrinsic motivation has not yet fully translated into active cognitive engagement due to the intervention of affective, social, and situational factors. Thus, Lesson Study and PBL have proven effective in fostering intrinsic motivation, but strengthening collaborative strategies is necessary to ensure optimal cognitive engagement for each individual.